Oxidative Stress Level in the Testes of Mice and Rats during Nickel Intoxication - Eugenia Murawska-Ciałowicz; Wojciech Bal; Lidia Januszewska; Marcin Zawadzki; Joanna Rychel; Jolanta Zuwała-Jagiełło (The Scientific World Journal)
The genotioxic and carcinogenic effect of nickel probably results from its capacity to produce reactive oxygen species (ROS) and disturb the redox balance. The aim of the study was to find out if rats lacking spermatic protamine 2 are less susceptible to Ni(II) than mice. Consequently, the levels of malondialdehyde + 4 hydroxynonenal (MDA+4HDA) − markers of lipid peroxidation, as well as the level of reduced glutathione (GSH) were measured within the rat and mouse testes. Our results showed that the levels of lipid peroxidation markers were elevated in testicular homogenates of intoxicated mice without any changes in rats. GSH level was lower in the group of intoxicated mice comparing to the control without statistically significant changes in rats’ homogenates. Moreover, the level of GSH in the testes of intoxicated mice was lower than in rats. On the basis of our results, it appears that Ni(II) can initiate oxidative stress in the testes of mice but not of rats and can reduce GSH level. Consequently, the antioxidative defense of the testes is reduced. Ni(II) that causes oxidative stress in the testes may also contribute to infertility.